Group IV metal clusters as discrete building blocks for the synthesis of metal-organic frameworks - Ollier de Marichard, Alexandre (2022)
This thesis shows my investigations into the formation of metal-organic frameworks from discrete group IV metal clusters. To that end, three clusters were synthesised, namely Zr6 benzoate, Zr6 methacrylate and Ti6 aminobenzoate. Novel clusters were synthesised, but poor crystallinity meant that they could not be fully characterised, and therefore were not suitable for further reactions.